Learning from the operation, pathology and maintenance of a bioretention system to optimize urban drainage practices. (15th December 2017) - de Macedo, Marina Batalini; Rosa, Altair; do Lago, César Ambrogi Ferreira; Mendiondo, Eduardo Mario; de Souza, Vladimir Caramori Borges
Abstract: LID practices for runoff control are increasingly being used as an integrated solution in urban drainage, helping to achieve hydrological balance close to the pre-urbanized period and decrease the diffuse pollution transported to urban rivers. Regarding bioretention, there is already broad knowledge about the detention of peak flows and their treatment capacity for many pollutants. However, there are still few field studies in microdrainage scale, which analyze the actual operation of these devices and raise common problems found, especially in subtropical climate. Therefore, this study aims to show what was learnt from the field operation of a bioretention cell on a micro-drainage scale, located in an urban catchment of a Brazilian city, suggesting maintenance actions as adaptations to the pathologies found. Five rainy events were monitored during the dry season, in order to carry out a preliminary analysis for critical conditions in terms of maintenance and diffuse pollution accumulation. From the first water balance results, low storage and low infiltration capacity of the soil were found as main pathologies. They led to a great amount of runoff passing directly through the cell surface and at a high velocity, resulting in soil erosion and low water retention efficiency. To overcome these problems, some structural adaptations were made over the cell, highlighting the semi-direct injection. The maintenance and adaptations proposed were suitable to avoid the erosion process, increasing the storage and improving the water retention efficiency in bioretention. They should be considered from the very initial stages, to using sites with low permeability. Highlights: Bioretention effectiveness in subtropical climate can be affected by the soil characteristics and composition. Maintenance needs and adaptations are proposed for bioretention systems in highly weathered soils. The maintenance proposed contributes to an increase of 70% in the stored volume in the bioretention basin.